Does intellectual capital matter in performance management system-organizational performance relationship? Experience of higher education institutions in Indonesia - Bambang Tjahjadi (Emerald Publishing Limited, 2019)
Purpose The purpose of this paper is to investigate whether performance management system (PMS) has a positive effect on organizational performance. Furthermore, it also investigates whether intellectual capital (IC) mediates PMS-organizational performance relationship.